Integrated Biomedical and Holistic Management of Bilateral Knee Osteoarthritis with Hypertension in a 71-Year-Old Woman: A Case-Based Analysis - Yessi Nurmalasari; Famela Mutiarasari; Faradillah Puspitasari; Fauziatus Sabila; Fernando Hoky Saputra; Feni Fadila (Biomedical Research and Theory Letters, 2025)
Bilateral knee osteoarthritis is a progressive degenerative joint condition frequently observed in the elderly and often complicated by comorbid hypertension, which can exacerbate systemic inflammation and impair functional outcomes. This case report presents a 71-year-old woman with acute worsening of bilateral knee pain and restricted flexion over three days, accompanied by neck discomfort. Her medical history included longstanding hypertension and a positive maternal family history of the same condition. A holistic, family-medicine–based assessment revealed interacting biomedical factors (pain, limited mobility, elevated blood pressure), psychological concerns related to fear of functional decline, adequate family and social support, and environmental-behavioral contributors affecting daily activities. The patient underwent integrated management consisting of patient education, lifestyle modification, joint-protective behavior counseling, and tailored low-intensity physical exercise. Pharmacological therapy included sodium diclofenac 50 mg, amlodipine 5 mg, dexamethasone 0.5 mg, and pyridoxine HCl. Follow-up evaluation demonstrated reduced pain intensity, improved knee mobility, better hypertension control, and enhanced disease understanding, indicating positive response to combined biomedical and holistic interventions. This report aims to document the identification, management, and clinical progression of bilateral knee osteoarthritis with comorbid hypertension using a structured family medicine approach. A literature review indicates that osteoarthritis progression in the elderly is commonly influenced not only by degenerative aging processes and obesity but also by comorbidities such as hypertension, which may worsen joint microcirculation, increase inflammatory mediators, and accelerate cartilage degradation. The novelty of this report lies in the integration of a comprehensive holistic assessment encompassing biomedical, psychological, social, and behavioral dimensions into the management plan, demonstrating its measurable impact on short-term clinical improvement. This case underscores that elderly patients with coexisting osteoarthritis and hypertension benefit significantly from an interdisciplinary, patient-centered model of care. The findings support that early holistic intervention may optimize functional capacity, enhance self-management, and potentially slow the progression of disability, offering valuable insights for future community-based geriatric care frameworks.